Reforma a vapor do propano com captura de dióxido de carbono utilizando catalisadores a base de níquel e óxido de cálcio - Oliveira, Ana Caroline Pereira (2019)
The use of bifunctional catalysts to carbon dioxide (CO2) capture with concomitant hydrocarbon steam reform has been proposed as a possible option to improve hydrogen yield (H2) and decrease CO2 emissions. In this study, the performance of bifunctional catalysts of Ni over CaO, CaO-CaZrO3 and CaO-Ca2SiO4 were tested in CO2 capture and sorption-enhanced steam propane reforming cycles. The catalysts were synthesized by sol-gel technique and characterized by X-ray Diffraction (XRD) ex situ and in situ, Scanning Electron Microscopy (SEM), and X-Ray Absorption Spectroscopy (XAS) in situ. Both tests confirmed a significant improvement in the thermal stability of the catalysts containing ZrO2 and SiO2. The reason is the minimization of CaO sintering due to the higher thermal stability added by the formation of CaZrO3 and Ca2SiO4 and avoiding contact between the CaO particles. The catalyst containing silica, although it has a lower percentage of free CaO, and a shorter period before saturation in terms of CO2 capture (pre-breakthrough), produced a higher purity H2, both in pre-breakthrough and post-breakthrough, with purities close to 95 and 80%, respectively. On the other hand, the catalyst containing zirconia showed better CO2 capture since the second cycle than Ni/Ca catalyst and stable pre-breakthrough time, around 50 minutes. The formation of the mixed oxides CaZrO3 and Ca2SiO4 favored the thermal stability of the catalysts both in the carbonation and reaction tests. The thermogravimetric (TGA) tests, after the reaction cycles, also showed that presence of the mixed oxides CaZrO3 and Ca2SiO4 in the catalysts probably minimized formation of coke on catalysts surface, from 3.6 to 1.3 and 1.5 mgC/gcat/h, for the Ni/Ca, Ni/CaZr, and Ni/CaSi catalysts, respectively.